A review on the buyer–supplier dyad relationships in sustainable procurement context: past, present and future. Issue 5 (3rd March 2016) - Ghadimi, Pezhman; Azadnia, Amir Hossein; Heavey, Cathal; Dolgui, Alexandre; Can, Birkan
Abstract : Sustainable development is currently being applied in most fields of research. Procurement, focused on the buyer–supplier dyad, is one such discipline where sustainability is being widely applied. This paper provides a review of these research studies, conducting a systematic content analysis in order to present the state of the art in this domain. The paper carries out a detailed review of articles in international scientific journals and well-known international conferences related to green and sustainable supplier selection published between 2008 and 2014 inclusive. Seven designed research questions are proposed and answered based on this bibliography. Interesting results are reported in each section and gaps in the current body of literature are identified. The purpose of this review is to provide important future directions and limitations in this research topic.